Method for calcium salt activation conversion and high-value utilization of waste lithium iron phosphate battery material
After calcium salt activation and dilute sulfuric acid system refinement, the calcium-iron base geological polymer was prepared by compound transformation, which solved the problems of recycling and high-value utilization of waste lithium iron phosphate battery materials, and achieved efficient recycling and high-value-added products. preparation.
Patent Information
- Application Number
- CN202310950698.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-31
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-07-31
AI Technical Summary
The prior art is difficult to effectively recycle and use waste lithium iron phosphate battery materials at a high value, resulting in low added value and easy pollution.
Calcium salt activation is carried out by mixing waste lithium iron phosphate battery material with oxidized calcium salt in a high-speed ball mill, then iron-lithium fractionation is performed in dilute sulfuric acid system, and finally iron-calcium enrichment is combined with aggregate and other materials. Transformation, prepare calcium-iron-based geological polymers.
It realizes efficient recycling and high-value utilization of waste lithium iron phosphate battery materials, improves the recovery rate of lithium elements, reduces pollution and disposal costs, and prepares new building materials with high added value.
Smart Images

Figure CN119430748A_ABST
Abstract
Description
Technical field:
[0001] The invention relates to the technical field of comprehensive utilization of waste lithium iron phosphate battery materials, and in particular to a method for activation, conversion and high-value utilization of calcium salts of waste lithium iron phosphate battery materials. Background technology:
[0002] Waste lithium iron phosphate battery materials are often leached with a strong acid and alkali system supplemented with an oxidant to achieve the purpose of lithium iron phosphate deconstruction, and a large amount of secondary solid waste enriched with elements such as iron, calcium, and phosphorus is often generated during the disposal process, which has the basic properties of low added value and easy pollution. Publication No. CN 114229812 A discloses a method for extracting iron and phosphorus from lithium iron phosphate waste, wherein the lithium iron phosphate waste is leached with an acidic oxidant system to obtain a low-purity lithium-rich solution and iron phosphate slag, and further reduced and transformed by a reducing agent and an auxiliary agent to achieve activation and transformation of the iron phosphate slag to obtain iron powder and phosphate. The recovery rate of iron and phosphorus in this method can only be as high as about 95%, and the recovery process is first oxidized and then reduced, which makes it difficult to achieve atomic economy and economic benefits. In addition, the iron-phosphorus enriched body obtained after industrial leaching of waste lithium iron phosphate battery materials is also used to prepare battery materials. Due to the high impurity content and low purity of iron phosphate, the obtained active materials are difficult to meet commercial requirements.
[0003] Geopolymer is a polymer gel made from minerals or solid waste. It has a wide range of adaptability to raw material sources, especially good compatibility with secondary solid waste rich in calcium, iron, phosphorus, sulfur and other components. It also has excellent mechanical properties and fire resistance, high temperature resistance, acid and alkali resistance, and has broad application prospects in the fields of bulk industrial solid waste disposal. Based on the above analysis, it is of great significance to replace natural minerals with by-products produced in the recycling process of waste lithium iron phosphate battery materials to prepare geopolymer raw materials and realize the transformation of low value-added products to high value-added products in the lithium iron phosphate recycling industry.
[0004] Therefore, it is necessary to develop a high-efficiency, low-pollution recycling system to solve the problem of clean recycling of waste lithium iron phosphate battery materials and high-value utilization of all components. Summary of the invention:
[0005] The purpose of the present invention is to provide a method for activating, transforming and high-value utilization of calcium salt of waste lithium iron phosphate battery materials.
[0006] The present invention is achieved through the following technical solutions:
[0007] A method for activating, converting and high-value utilization of calcium salt of waste lithium iron phosphate battery materials, the method comprising the following steps:
[0008] (1) Calcium salt activation: The waste lithium iron phosphate battery material and the oxidative calcium salt are fully mixed in a high-speed ball mill for calcium salt activation;
[0009] (2) Iron-lithium separation: adding dilute sulfuric acid to the product after calcium salt activation in step (1) to prepare a slurry, mechanically strengthening stirring, and then diaphragm filtering to achieve iron-lithium separation to obtain an iron-calcium-rich body and a lithium-rich liquid, and the lithium-rich liquid is returned to the lithium salt purification process;
[0010] (3) Compounding and transformation: The iron-calcium enriched body obtained in step (2) is mixed with aggregate, activator, stimulator, and tap water in a certain proportion in a mixer and mechanically stirred for compounding and transformation to obtain a slurry prepolymer; the total mass percentage of the raw materials is 100%, the content of the iron-calcium enriched body is 20-30%, the content of the aggregate is 10-20%, the content of the activator is 10-17%, the content of the stimulator is 5-15%, and the content of the tap water is 32-40%;
[0011] (4) Forming and curing: injecting the slurry precursor obtained in step (3) into a mold, placing the mold in a constant temperature and humidity chamber for forming and curing, and then demolding to obtain a calcium iron-based geopolymer.
[0012] Preferably, the waste lithium iron phosphate battery material is leftover material generated during the production of lithium iron phosphate batteries and / or the positive electrode material after disassembly and sorting of retired lithium iron phosphate batteries.
[0013] Preferably, the oxidizing calcium salt described in step (1) is calcium hypochlorite and / or super calcium oxide, and the amount of oxidizing calcium salt added is 10wt% to 50wt% of the mass of the waste lithium iron phosphate battery material.
[0014] Preferably, the speed of the high-speed ball mill in step (1) is 500 rpm to 850 rpm, and the reaction time is 20 min to 65 min.
[0015] Preferably, the liquid-to-solid ratio of the product after activation of the dilute sulfuric acid and calcium salt in step (2) is 10:1 to 15:1 L / Kg.
[0016] Preferably, the mechanical stirring speed in step (2) is 180 rpm to 300 rpm, and the stirring time is 30 min to 90 min.
[0017] Preferably, the concentration of the dilute sulfuric acid in step (2) is 0.1M to 1.0M, more preferably 0.3M.
[0018] Preferably, the aggregate in step (3) is at least one of coal gangue, fly ash, and iron aluminum alum slag.
[0019] Preferably, the activator in step (3) is at least one of volcanic ash and desulfurized gypsum.
[0020] Preferably, the activator in step (3) is at least one of water glass and quicklime.
[0021] Preferably, the mechanical stirring speed in step (3) is 1000 rpm to 1800 rpm, and the stirring time is 5 to 25 min.
[0022] Preferably, the temperature in the constant temperature and humidity chamber in step (4) is 55° C. to 65° C., the humidity is 70% to 95%, and the curing time is 18 h to 48 h.
[0023] Compared with the prior art, the present invention has the following advantages:
[0024] 1. Compared with the traditional liquid-solid reaction of adding oxidants such as hydrogen peroxide, hypochlorous acid or chlorine to a volatile hydrochloric acid system, the present invention adopts chemically stable oxidizing calcium salts such as calcium hypochlorite and super calcium oxide to assist mechanochemical activation to strengthen the physical deconstruction of lithium iron phosphate, and then strengthens the selective leaching of lithium elements through a dilute sulfuric acid system, and simultaneously realizes the directional enrichment of phosphorus, iron elements and calcium and sulfur elements introduced into the system. It not only shortens the process, but also reduces the tail liquid disposal cost caused by repeated addition of chemical reagents to adjust the pH of the leachate neutralization reaction and reduces the loss of lithium elements. It has friendly operating environment, high lithium element recovery rate, is conducive to industrial application and promotion, and has significant economic benefits.
[0025] 2. The present invention uses the iron-calcium enriched body enriched with phosphorus, iron, calcium and sulfur elements produced in the recycling process of waste lithium iron phosphate battery materials as the geopolymer precursor, and couples typical industrial solid waste volcanic ash, desulfurized gypsum, coal gangue, fly ash, iron aluminum alum slag and the like as the aggregate and activator of the geopolymer, and obtains a new type of calcium-iron-based polymer gel material with high polymerization degree through the depolymerization and polycondensation reaction of oxides such as silicon, aluminum, calcium and iron in the mixed system, thus achieving the effect of "waste treatment with waste" and high value utilization. In particular, the iron-calcium enriched body produced in the recycling process of waste lithium iron phosphate battery materials can provide rich phosphorus, iron, calcium and sulfur elements, avoid the mining of natural ores, and reduce the disposal risk and cost of secondary pollutants such as iron-calcium enriched bodies; in addition, the main elements in the calcium-iron enriched body exist in the form of insoluble stable compounds, which improves the structural stability of high value-added products, ensures the stable chemical properties of the calcium-iron-based enriched body, and has a new type of building material with high value, low carbon and environmental protection.
[0026] Therefore, the technical solution proposed in the present invention is a linkage coupling method, which is particularly suitable for the comprehensive disposal of solid waste in the production, processing and recycling process of waste lithium iron phosphate batteries, as well as the low-carbon and clean production of new building materials of calcium-iron-based geopolymers. It has the characteristics of low carbon, environmental protection, high comprehensive resource utilization rate, low disposal cost and easy industrial application and promotion. Description of the drawings:
[0027] Figure 1It is a process flow chart of the present invention;
[0028] Figure 2 This is the XRD phase composition diagram of the iron-calcium rich body obtained in Example 3 of the present invention. Specific implementation method:
[0029] The following is a further description of the present invention, rather than a limitation of the present invention.
[0030] The composition of the waste lithium iron phosphate battery materials used in Examples 1-6 is shown in Table 1.
[0031] Table 1
[0032]
[0033]
[0034] Embodiment 1:
[0035] like Figure 1 As shown, a method for activating and converting calcium salt of waste lithium iron phosphate battery materials and high-value utilization includes the following steps:
[0036] (1) Calcium salt activation: The scraps generated during the production of lithium iron phosphate batteries are fully mixed with calcium hypochlorite in a high-speed ball mill for calcium salt activation, wherein the amount of calcium hypochlorite added is 10wt% of the mass of the scraps generated during the production of lithium iron phosphate batteries, the speed of the high-speed ball mill is 500rpm, and the reaction time is 20min;
[0037] (2) Iron-lithium separation: the product after calcium salt activation in step (1) is added with 0.1M dilute sulfuric acid to prepare a slurry, and after mechanical intensive stirring, the iron-lithium separation is achieved by diaphragm filter pressing to obtain an iron-calcium rich body and a lithium-rich liquid, and the lithium-rich liquid is returned to the lithium salt purification step; wherein the liquid-to-solid ratio of the product after dilute sulfuric acid and calcium salt activation is 10:1 L / Kg, the mechanical stirring speed is 180 rpm, and the stirring time is 30 min;
[0038] (3) Compounding and transformation: The iron-calcium enriched body obtained in step (2) is mixed with aggregate coal gangue, activator volcanic ash, activator water glass, and tap water in a blender at a mass percentage of 25:20:15:5:35 wt%, and stirred at a stirring speed of 1000 rpm for 5 min to compound and transform, thereby obtaining a slurry prepolymer;
[0039] (4) Molding and curing: The slurry precursor obtained in step (3) is injected into a 15 mm × 15 mm × 25 mm mold, and the mold is placed in a constant temperature and humidity chamber at a temperature of 55°C and a humidity of 70% for molding and curing, and then demolded. The curing time is 18 hours to obtain a calcium iron-based geopolymer.
[0040] Example 2
[0041] like Figure 1 As shown, a method for activating and converting calcium salt of waste lithium iron phosphate battery materials and high-value utilization includes the following steps:
[0042] (1) Calcium salt activation: The cathode material after disassembly and sorting of retired lithium iron phosphate batteries and super calcium oxide are fully mixed in a high-speed ball mill for calcium salt activation, wherein the amount of super calcium oxide added is 50wt% of the mass of the cathode material after disassembly and sorting of retired lithium iron phosphate batteries, the speed of the high-speed ball mill is 850rpm, and the reaction time is 65min;
[0043] (2) Iron-lithium separation: the product after calcium salt activation in step (1) is added with 1.0M dilute sulfuric acid to prepare a slurry, and after mechanical intensive stirring, the iron-lithium separation is achieved by diaphragm filter pressing to obtain an iron-calcium rich body and a lithium-rich liquid, and the lithium-rich liquid is returned to the lithium salt purification step, wherein the liquid-to-solid ratio of the product after dilute sulfuric acid and calcium salt activation is 15:1 L / Kg, the mechanical stirring speed is 300 rpm, and the stirring time is 90 min;
[0044] (3) Compounding and transformation: the iron-calcium enriched body obtained in step (2) is mixed with aggregate fly ash, activator desulfurized gypsum, activator quicklime, and tap water in a blender at a mass percentage of 30:10:10:10:40 (wt%), and stirred at a stirring speed of 1800 rpm for 25 min to obtain a slurry prepolymer;
[0045] (4) Molding and curing: The slurry precursor obtained in step (3) is injected into a 15 mm × 15 mm × 25 mm mold, and the mold is placed in a constant temperature and humidity chamber at a temperature of 65° C. and a humidity of 95% for molding and curing, and then demolded. The curing time is 48 hours to obtain a calcium iron-based geopolymer.
[0046] Example 3
[0047] like Figure 1 As shown, a method for activating and converting calcium salt of waste lithium iron phosphate battery materials and high-value utilization includes the following steps:
[0048] (1) Calcium salt activation: The scraps generated during the production of lithium iron phosphate batteries are fully mixed with super calcium oxide in a high-speed ball mill for calcium salt activation, wherein the amount of super calcium oxide added is 20wt% of the mass of the scraps generated during the production of lithium iron phosphate batteries, the speed of the high-speed ball mill is 600rpm, and the reaction time is 30min;
[0049] (2) Iron-lithium separation: The product after calcium salt activation in step (1) is added with 0.3M dilute sulfuric acid to prepare a slurry, and after mechanical intensive stirring, diaphragm filter pressing is used to achieve iron-lithium separation to obtain an iron-calcium rich body and a lithium-rich liquid, and the lithium-rich liquid is returned to the lithium salt purification step; wherein the liquid-to-solid ratio of the product after dilute sulfuric acid and calcium salt activation is 11:1 L / Kg, the mechanical stirring speed is 200 rpm, and the stirring time is 40 min. The XRD phase composition of the obtained iron-calcium rich body is as follows: Figure 2 As shown;
[0050] (3) Compounding and transformation: the iron-calcium enriched body obtained in step (2) is mixed with the aggregate iron aluminum alum slag, the activator volcanic ash, the activator quicklime, and tap water in a blender at a weight percentage (wt%) of 20:15:15:15:35, and the mixture is stirred at a stirring speed of 1200 rpm for 10 min to obtain a slurry prepolymer;
[0051] (4) Molding and curing: The slurry precursor obtained in step (3) is injected into a 15 mm × 15 mm × 25 mm mold, and the mold is placed in a constant temperature and humidity chamber at a temperature of 60° C. and a humidity of 75% for molding and curing, and then demolded. The curing time is 24 hours to obtain a calcium iron-based geopolymer.
[0052] Example 4
[0053] like Figure 1 As shown, a method for activating and converting calcium salt of waste lithium iron phosphate battery materials and high-value utilization includes the following steps:
[0054] (1) Calcium salt activation: The cathode material of the retired lithium iron phosphate battery after disassembly and sorting is fully mixed with calcium hypochlorite in a high-speed ball mill for calcium salt activation, wherein the amount of calcium hypochlorite added is 45wt% of the weight of the scraps generated during the production process of the lithium iron phosphate battery, the speed of the high-speed ball mill is 750rpm, and the reaction time is 50min;
[0055] (2) Iron-lithium separation: the product after calcium salt activation in step (1) is added with 0.8M dilute sulfuric acid to prepare a slurry, and after mechanical intensive stirring, the iron-lithium separation is achieved by diaphragm filter pressing to obtain an iron-calcium rich body and a lithium-rich liquid, and the lithium-rich liquid is returned to the lithium salt purification step; wherein the liquid-to-solid ratio of the product after dilute sulfuric acid and calcium salt activation is 14:1 L / Kg, the mechanical stirring speed is 250 rpm, and the stirring time is 75 min;
[0056] (3) Compounding and transformation: the iron-calcium enriched body obtained in step (2) is mixed with aggregate fly ash, activator desulfurized gypsum, activator water glass, and tap water in a blender at a weight percentage (wt%) of 28:18:17:5:32, and stirred at a stirring speed of 1600 rpm for 20 minutes to obtain a slurry prepolymer;
[0057] (4) Molding and curing: The slurry precursor obtained in step (3) is injected into a 15 mm × 15 mm × 25 mm mold, and the mold is placed in a constant temperature and humidity chamber at a temperature of 65°C and a humidity of 80% for molding and curing, and then demolded. The curing time is 30 hours to obtain a calcium iron-based geopolymer.
[0058] Example 5
[0059] like Figure 1 As shown, a method for activating and converting calcium salt of waste lithium iron phosphate battery materials and high-value utilization includes the following steps:
[0060] (1) Calcium salt activation: The cathode material after disassembly and sorting of retired lithium iron phosphate batteries was fully mixed with calcium hypochlorite in a high-speed ball mill for calcium salt activation, wherein the amount of calcium hypochlorite added was 25wt% of the mass of the cathode material after disassembly and sorting of retired lithium iron phosphate batteries, the speed of the high-speed ball mill was 650rpm, and the reaction time was 35min;
[0061] (2) Iron-lithium separation: the product after calcium salt activation in step (1) is added with 0.5M dilute sulfuric acid to prepare a slurry, and after mechanical intensive stirring, the iron-lithium separation is achieved by diaphragm filter pressing to obtain an iron-calcium rich body and a lithium-rich liquid, and the lithium-rich liquid is returned to the lithium salt purification step; wherein the liquid-to-solid ratio of the product after dilute sulfuric acid and calcium salt activation is 12:1 L / Kg, the mechanical stirring speed is 220 rpm, and the stirring time is 50 min;
[0062] (3) Compounding and transformation: The iron-calcium enriched body obtained in step (2) is mixed with the aggregate iron aluminum alum slag, the activator volcanic ash, the activator quicklime, and tap water in a blender in a weight percentage (wt%) of 26:13:11:13:37, and the mixture is stirred at a stirring speed of 1500 rpm for 15 minutes to obtain a slurry prepolymer;
[0063] (4) Molding and curing: The slurry precursor obtained in step (3) is injected into a 15 mm × 15 mm × 25 mm mold, and the mold is placed in a constant temperature and humidity chamber at a temperature of 55° C. and a humidity of 90% for molding and curing, and then demolded. The curing time is 36 hours to obtain a calcium iron-based geopolymer.
[0064] Example 6
[0065] like Figure 1 As shown, a method for activating and converting calcium salt of waste lithium iron phosphate battery materials and high-value utilization includes the following steps:
[0066] (1) Calcium salt activation: The scraps generated during the production of lithium iron phosphate batteries are fully mixed with super calcium oxide in a high-speed ball mill for calcium salt activation, wherein the amount of super calcium oxide added is 35wt% of the mass of the scraps generated during the production of lithium iron phosphate batteries, the speed of the high-speed ball mill is 550rpm, and the reaction time is 45min;
[0067] (2) Iron-lithium separation: the product after calcium salt activation in step (1) is added with 0.6M dilute sulfuric acid to prepare a slurry, and after mechanical intensive stirring, the iron-lithium separation is achieved by diaphragm filter pressing to obtain an iron-calcium rich body and a lithium-rich liquid, and the lithium-rich liquid is returned to the lithium salt purification step; wherein the liquid-to-solid ratio of the product after dilute sulfuric acid and calcium salt activation is 13:1 L / Kg, the mechanical stirring speed is 270 rpm, and the stirring time is 60 min;
[0068] (3) Compounding and transformation: The iron-calcium enriched body obtained in step (2) is mixed with aggregate coal gangue, activator desulfurized gypsum, activator quicklime, and tap water in a blender at a weight percentage (wt%) of 24:11:13:14:38, and stirred at a stirring speed of 1500 rpm for 17 minutes to obtain a slurry prepolymer;
[0069] (4) Molding and curing: The slurry precursor obtained in step (3) is injected into a 15 mm × 15 mm × 25 mm mold, and the mold is placed in a constant temperature and humidity chamber at a temperature of 62° C. and a humidity of 85% for molding and curing, and then demolded. The curing time is 40 hours to obtain a calcium iron-based geopolymer.
[0070] Comparative Example 1
[0071] Refer to Example 1, except that no oxidizing calcium salt is added in the calcium salt activation process in step (1), and tap water is used instead of dilute sulfuric acid solution in the iron-lithium separation process in step (2). The remaining processes and parameters are the same as those in Example 1.
[0072] Since no oxidizing calcium salt is added in the calcium salt activation in Comparative Example 1, and tap water is used as the solvent in the iron-lithium separation process, the lithium iron phosphate is incompletely decomposed, the lithium recovery rate is low, and the obtained leaching residue fails to enrich the necessary geopolymer components such as calcium and sulfur, resulting in poor flexural and compressive strength properties of the obtained geopolymer, the product is unqualified, and the purpose of high value cannot be achieved.
[0073] Comparative Example 2
[0074] Refer to Example 3, the difference is that in step (2) the iron-lithium separation process uses 0.3M dilute nitric acid instead of dilute sulfuric acid solution, and in step (3) the compounding and transformation process, the iron-calcium enriched body and the aggregate iron aluminum alum slag, the activator volcanic ash, the activator (not used), and the tap water are mixed in a blender at a mass percentage (wt%) of 20:20:20:0:40, and the compounding and transformation is carried out at a stirring speed of 1000 rpm for 30 minutes. The remaining processes and parameters are the same as those in Example 3.
[0075] Since 0.3M dilute nitric acid is used instead of dilute sulfuric acid solution in the iron-lithium fine separation process in Comparative Example 2, although the lithium element has a higher leaching rate, the leaching residue fails to enrich the necessary geopolymer components such as calcium and sulfur due to the nitration of nitric acid, and the addition of nitric acid causes the dispersion of iron elements, the iron content in the leaching residue decreases, and the iron concentration in the leachate increases, resulting in incomplete separation of lithium and iron, requiring an additional impurity removal process to improve the purity of lithium in the leachate. In addition, since activators such as quicklime or water glass are not used in the composite transformation process, demolding is difficult during the molding and curing process, and the molded geopolymer cannot be obtained, the product is unqualified, and the purpose of high value cannot be achieved.
[0076] The lithium recovery rates in Examples 1 to 6 and Comparative Examples 1 to 2 and the 3-day and 7-day performance test indicators of the obtained calcium-iron-based polymers are shown in Table 2:
[0077] Table 2
[0078]
[0079]
[0080] The description of the above embodiments is only used to help understand the technical solution and core ideas of the present invention. It should be pointed out that for technicians in this technical field, several improvements and modifications can be made to the present invention without departing from the principles of the present invention. These improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A method for activating, converting and high-value utilization of calcium salt of waste lithium iron phosphate battery materials, characterized in that: The method comprises the following steps: (1) Calcium salt activation: The waste lithium iron phosphate battery material and the oxidative calcium salt are fully mixed in a high-speed ball mill for calcium salt activation; (2) Iron-lithium separation: the product after calcium salt activation in step (1) is added with dilute sulfuric acid to prepare a slurry, and after mechanical intensive stirring, diaphragm filter pressing is used to achieve iron-lithium separation to obtain an iron-calcium-rich body and a lithium-rich liquid, and the lithium-rich liquid is returned to the lithium salt purification process; (3) Compounding and transformation: The iron-calcium enriched body obtained in step (2) is mixed with aggregate, activator, stimulator, and tap water in a certain proportion in a mixer and mechanically stirred for compounding and transformation to obtain a slurry prepolymer; the total mass percentage of the raw materials is 100%, the content of the iron-calcium enriched body is 20-30%, the content of the aggregate is 10-20%, the content of the activator is 10-17%, the content of the stimulator is 5-15%, and the content of the tap water is 32-40%; (4) Forming and curing: injecting the slurry precursor obtained in step (3) into a mold, placing the mold in a constant temperature and humidity chamber for forming and curing, and then demolding to obtain a calcium iron-based geopolymer.
2. The method according to claim 1, characterized in that The waste lithium iron phosphate battery material is the leftovers generated in the production process of lithium iron phosphate batteries and / or the positive electrode material after disassembly and sorting of retired lithium iron phosphate batteries.
3. The method according to claim 1, characterized in that: The oxidizing calcium salt is calcium hypochlorite and / or super calcium oxide, and the added amount of the oxidizing calcium salt is 10wt% to 50wt% of the mass of the waste lithium iron phosphate battery material.
4. The method according to claim 1, characterized in that: The speed of the high-speed ball mill in step (1) is 500 rpm to 850 rpm, and the reaction time is 20 min to 65 min.
5. The method according to claim 1, characterized in that: The liquid-to-solid ratio of the product after activation of the dilute sulfuric acid and calcium salt in step (2) is 10:1 to 15:1 L / Kg.
6. The method according to claim 1, characterized in that The concentration of the dilute sulfuric acid in step (2) is 0.1M to 1.0M.
7. The method according to claim 1, characterized in that The mechanical stirring speed in step (2) is 180 rpm to 300 rpm, and the stirring time is 30 min to 90 min.
8. The method according to claim 1, characterized in that: In step (3), the aggregate is at least one of coal gangue, fly ash, and iron aluminum alum slag; the activator is at least one of volcanic ash and desulfurized gypsum; and the stimulator is at least one of water glass and quicklime.
9. The method according to claim 1, characterized in that The mechanical stirring speed of step (3) is 1000 rpm to 1800 rpm, and the stirring time is 5 to 25 min.
10. The method according to claim 1, characterized in that The temperature in the constant temperature and humidity box in step (4) is 55° C. to 65° C., the humidity is 70% to 95%, and the curing time is 18 h to 48 h.
Citation Information
Patent Citations
Method for extracting iron and phosphorus from lithium iron phosphate waste
CN114229812A
Method for recovering lithium in waste and old lithium iron phosphate batteries
CN106848472A
Method for recovering aluminum from lithium iron phosphate positive electrode material, obtained material and application
CN114292044A
Polar Vector Modulator and Variable Gain Phase Shifter Using The Same
KR1020240141959A
Processes for recycling spent catalysts, recycling rechargeable batteries, and integrated processes thereof
US11682801B1